How much water am I using for my yard? - Nicholas Taylor; Kaitlin Robb Price; Bradley Spatz (EDIS, 2023)
This publication provides context and motivation for reducing outdoor water use. This is done by providing the estimated gallons of water used per irrigation cycle in Florida and then comparing the water used for irrigation to the water used for common indoor activities like showering or washing dishes.